Effects of high-fiber food product consumption and personal health record use on body mass index and bowel movement - Mamoru Ito; Joto Yoshimoto; Tetsuya Maeda; Sho Ishii; Yu Wada; Mikiya Kishi; Takashi Koikeda (Journal of Functional Foods, 2023)
A health program including consumption of high-fiber ZENB Noodles (ZN) and ZENB Sticks (ZS), combined with the use of a personal health record (PHR) was employed; effects on body mass index (BMI) and bowel movement were evaluated. Fifty-nine healthy adults with overweight (mean baseline BMI, 27.0 kg/m2) participated and consumed ZN and ZS once daily, five days/week for 12 weeks and tracked their dietary intake, body weight, and blood pressure using a mobile PHR application (Welby My Carte). Mean BMI decreased significantly to 26.8 kg/m2 at 8 weeks (p = 0.031). The mean number of weekly bowel movements per participant increased significantly from 6.95 at baseline to 8.78, 8.34, and 8.58 at 4, 8, and 12 weeks, respectively (all p < 0.001). Thus, high-fiber food product consumption and PHR use decreased BMI and improved bowel movement among healthy adults with overweight. This study was registered in the UMIN Clinical Trials Registry (UMIN trial ID:UMIN000040105).